Romania: The Relationship Between Tax Legislation, Tax Competition, and Sovereignty - Cîrmaciu, Diana (Economic Governance: The Impact of the European Union on the Regulation of Fiscal and Monetary Policy in Central European Countries, 2024)
Dealing with a topic related to taxation involves engaging complex issues, both in terms of incidental legislation and its role (i.e. its economic and social functions). The state plays a decisive role in economic development, but its intervention in this field must not have a restrictive character, evident in the adoption of rigid – and sometimes even arbitrary – legal provisions. Interventions in the economy, which have a long history, are done naturally according to emerging needs, assuming the implementation of a predictable fiscal policy to adapt the business environment to the challenges of the contemporary period (e.g. economic crises, health crises, armed conflicts). When, for various reasons, economic values are overturned, reform is necessary to bring the economic sphere into harmony with legal norms, which must then be recovered and developed. In light of these ideas, this study briefly analyses the state of fiscal legislation in Romania and clarifies related technical terms and definitions. We follow the trends in Romanian taxation, the fiscal policies which the governors assume, and the measures to ensure budget revenue (these measures are not always popular, but are arranged for the benefit of the general interests of the community). The field of taxation often raises problems, and such analyses can yield ways to implement combinations of taxes that enable public authorities to cover budgetary needs (taking into account the nation’s level of development and specific economic features).Keywords: tax legislation, taxes, the Fiscal Code, fiscal sovereignty, tax fraud